Clinical observations of tetanus toxin plus decoy, Snoretox-1, a novel targeted neuromuscular stimulant, in a pilot study of 6 British bulldogs with BOAS - Anthony Sasse; Luke J. Norbury; Thomas McLean; Maurice Newport; Arthur House; David W. Swift; Danny Aliano; Peter M. Smooker; Russell Conduit (The Veterinary Journal, 2026)

Nest site and habitat changes over 15 years in a predicted climate refugium in Beluga, AK, USA, have a positive impact on Hudsonian godwit (Limosa haemastica) nest survival - Eden Smith; Rose J. Swift; Anna Courtemanche; Feipeng Huang; Mary Margaret Pelton; Lauren Puleo; Josiah Simmons; Matthew M. Waller; Hannah Walton; Casey Weissburg; Luke R. Wilde; Nathan R. Senner (Polar Biology, 2026)

The mismatch between swimming speeds and flow regimes when optimising exercise regimes to improve Chinook salmon, Oncorhynchus tshawytscha, performance - Leteisha A. Prescott; Jane E. Symonds; Seumas P. Walker; Matthew R. Miller; Luke Swift; Neill A. Herbert; Jayson M. Semmens; Chris G. Carter (Aquaculture, 2024)

Application and Validation of Flood Damage Curves for Wastewater Treatment Facilities (WWTF), Case Examples in Rhode Island - Tyler Donahue; Peter Krekorian; Luke Swift; Malcolm L. Spaulding; Chris Baxter; Craig Swanson (Journal of Marine Science and Engineering, 2022)
The STORMTOOLS Coastal Environmental Risk Index (CERI) has historically been used to assess the damage to residential and commercial structures from coastal flooding, including the effects of sea level rise (SLR) in RI. In the present study, CERI was extended to address the impact of flooding for 100 yr storm, including the effects of SLR, to the newly renovated Warren, RI wastewater treatment facilities (WWTF), located on the tidal Warren River, using FEMA HAZUS damage curves. The analysis shows that the average damage for 100 yr flooding, across all components of the facility, increases with sea level from 16% (0 ft SLR), 23% (2 ft SLR), 26% (3 ft SLR), to 28% (5 ft SLR). The primary settling and chlorination tanks are at most risk and the aeration and reaction tanks at least risk. In an effort to validate the FEMA HAZUS WWTF damage curves, CERI was applied to predict flood damage during the 3 day, March/April 2010 flooding event (500 yr) to the Cranston, Warwick, and West Warwick WWTF located on the Pawtuxet River, RI. The predictions of the damage to each WWTF from this event were compared to observations of the damage made by the plant operators. The percent damage was estimated by comparing the cost of the damage to the assessed value of the facility. Using the FEMA HAZUS damage curves for the observed level of inundation (7 to 8 ft) predicted that the Warwick and West Warwick facility damage ranged from 15 to 45% with an average value of about 30%. The Cranston WWTF damage was very low (

Dynamic sensitivity to resource availability influences population responses to mismatches in a shorebird - Luke R. Wilde; Josiah E. Simmons; Rose J. Swift; Nathan R. Senner (Ecology, 2022)
Climate change has caused shifts in seasonally recurring biological events leading to the temporal decoupling of consumer–resource pairs, that is, phenological mismatching. Although mismatches often affect individual fitness, they do not invariably scale up to affect populations, making it difficult to assess the risk they pose. Individual variation may contribute to this inconsistency, with changes in resource availability and consumer needs leading mismatches to have different outcomes over time. Nevertheless, most models estimate a consumer's match from a single time point, potentially obscuring when mismatches matter to populations. We analyzed how the effects of mismatches varied over time by studying precocial Hudsonian godwit ( Limosa haemastica ) chicks and their invertebrate prey from 2009 to 2019. We developed individual‐ and population‐level models to determine how age‐specific variation affects the relationship between godwits and resource availability. We found that periods with abundant resources led to higher growth and survival of godwit chicks, but also that chick survival was increasingly related to the availability of larger prey as chicks aged. At the population level, estimates of mismatches using age‐structured consumer demand explained more variation in annual godwit fledging rates than more commonly used alternatives. Our study suggests that modeling the effects of mismatches as the disrupted interaction between dynamic consumer needs and resource availability clarifies when mismatches matter to both individuals and populations.